Emergence of wheat blast in Bangladesh was caused by a South American lineage of Magnaporthe oryzae - Islam, M.Tofazzal; Croll, Daniel; Gladieux, Pierre; Soanes, Darren M.; Persoons, Antoine; Bhattacharjee, Pallab; Hossain, Md.Shaid; Gupta, Dipali Rani; Rahman, Md.Mahbubur; Mahboob, M.Golam; Cook, Nicola; Salam, Moin U.; et al. (My University, 2016)
Background: In February 2016, a new fungal disease was spotted in wheat fields across eight districts in Bangladesh. The epidemic spread to an estimated 15,000 hectares, about 16% of the cultivated wheat area in Bangladesh, with yield losses reaching up to 100%. Within weeks of the onset of the epidemic, we performed transcriptome sequencing of symptomatic leaf samples collected directly from Bangladeshi fields. Results: Reinoculation of seedlings with strains isolated from infected wheat grains showed wheat blast symptoms on leaves of wheat but not rice. Our phylogenomic and population genomic analyses revealed that the wheat blast outbreak in Bangladesh was most likely caused by a wheat-infecting South American lineage of the blast fungus Magnaporthe oryzae. Conclusion: Our findings suggest that genomic surveillance can be rapidly applied to monitor plant disease outbreaks and provide valuable information regarding the identity and origin of the infectious agent.
Keywords: Eleusine indica; Field pathogenomics; Oryza sativa; Phylogenomic analysis; Wheat blast